COVID-19 Pandemic: The Impact of the Social Media Technology on Higher Education - Christos Papademetriou; Sofia Anastasiadou; George Konteos; Stylianos Papalexandris (MDPI AG, 2022)
The COVID-19 pandemic led universities to transform the traditional teaching methodologies into distance education. Therefore, social media has become progressively prominent as teaching and learning resources in universities. Several studies have been conducted for the development of social media as a learning tool. However, there is limited empirical evidence supporting this claim. The present study bridges the gap in the literature concerning the value of the use of social media in higher education. This research seeks to examine the impact of the use of social media in (a) enhancing teaching and learning in universities, (b) motivating and supporting students and (c) developing community connection. A qualitative methodology was adopted. Specifically, in-depth interviews were conducted to assess the effectiveness of social media on students learning in higher education. The results showed that the use of social media by higher educational institutions positively impacts the educational process by (a) promoting teaching and learning, (b) motivating students to be active participants, and (c) establishing connections in the university community. Some obstacles in the teaching and learning process were also identified. Future areas of research are proposed.